Bridge-Chlorinated Bicyclo[1.1.1]pentane-1,3-dicarboxylic Acids - Kaleta, Jiří; Rončević, Igor; Císařová, Ivana; Dračínský, Martin; Šolínová, Veronika; Kašička, Václav; Michl, Josef (The Journal of organic chemistry, 2019)
Radical chlorination of bicyclo[1.1.1]pentane-1,3-dicarboxylic acid is highly selective, and up to four chlorine atoms can be introduced relatively easily without damage to the strained bicyclic cage. Combined with hydrodechlorination with TMS3SiH, direct chlorination provides access to five of the 15 possible chlorinated diacids. Their configuration has been established by X-ray diffraction. Their p Ka values have been measured by capillary electrophoresis and calculated at the B3LYP-D3BJ/6-311+G(d,p)-level. The results are in good agreement and reflect the expected trend, from 2.78 ± 0.08 and 4.14 ± 0.10 in the parent to 1.07 ± 0.03 and 2.31 ± 0.03 in the tetrachlorinated diacid. Strain energy relative to the parent diacid was calculated for all 15 chlorinated diacids and shows a dramatic increase with successive chlorination, due to nonbonded Cl-Cl repulsions.